1997
DOI: 10.1023/a:1005809900758
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We have designed protein molecules based on an alpha-helical coiled-coil structure. These proteins can be tailored to complement nutritionally unbalanced seed meals. In particular, these proteins may contain up to 43% mol/mol of the essential amino acid lysine. Genes encoding such proteins were constructed using synthetic oligonucleotides and the protein stability was tested for in vivo by expression in an Escherichia coli model system. A protein containing 31% lysine and 20% methionine (CP 3-5) was expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…As a result, lysine content in seeds was increased in these transgenic tobacco seeds carrying one of these genes. However, lysine content was increased by less than 20% 26 , which might be due to that these genes encoded high lysine proteins with very small molecular weight (3–7 kDa). In this study, lysine/threonine-rich fragments consist of 73% and 83% of total amino acids with molecular weight at 78.7 kDa and 68.7 kDa in both TKTKK1 and TKTKK2 genes, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…As a result, lysine content in seeds was increased in these transgenic tobacco seeds carrying one of these genes. However, lysine content was increased by less than 20% 26 , which might be due to that these genes encoded high lysine proteins with very small molecular weight (3–7 kDa). In this study, lysine/threonine-rich fragments consist of 73% and 83% of total amino acids with molecular weight at 78.7 kDa and 68.7 kDa in both TKTKK1 and TKTKK2 genes, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…The application of synthetic biology on improving protein quality has been carried out long time ago. For example, several genes have been designed according to an alpha-helical coiled-coil structure and these genes encoded high lysine proteins 26 . As a result, lysine content in seeds was increased in these transgenic tobacco seeds carrying one of these genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression in soybean and canola seeds led to a notable increase of seed free lysine ( Falco et al , 1995 ). Among these early studies, Keeler et al (1997) also indicated that de novo expression of alpha-helical coiled-coil proteins might also increase the accumulation of lysine in mature tobacco seeds.…”
Section: Enhancing Lysine Levelsmentioning
confidence: 99%